Zredukuj:
a)3a+3b-c-4a-3b+2c
b) x²+2xy-3y²-2x²-y²-x²+2xy
c)⅙t²+⅓k²t+⅓tk²-k²t+½t²-⅙tk²
d)u²v²+¼uv-¹/₇u²v²-uv-½uv+u²v²

Zapisz bez nawiasów:
a) -(-a)+(-b)
b) -(-a)-(-b)
c)a+(-(-b))
d) a--(-(-b))
e) -(-(a-b))
f)a-(b-a)

3

Odpowiedzi

2010-03-09T22:23:38+01:00
Zredukuj:
a)3a+3b-c-4a-3b+2c = -a +c

b) x²+2xy-3y²-2x²-y²-x²+2xy = 2x² - 4y + 4xy

c)⅙t²+⅓k²t+⅓tk²-k²t+½t²-⅙tk² = 4/6 t²-2/3k²t + 2/6tk²

d)u²v²+¼uv-¹/₇u²v²-uv-½uv+u²v² = 3/7u²v²-5/4uv

Zapisz bez nawiasów:
a) -(-a)+(-b) = a-b
b) -(-a)-(-b) = a+b
c)a+(-(-b)) = a+b
d) a--(-(-b)) = a+b
e) -(-(a-b)) = a-b
f)a-(b-a) = a-b+a
2010-03-09T22:23:51+01:00
Zredukuj:
a)3a+3b-c-4a-3b+2c = -a+c

b) x²+2xy-3y²-2x²-y²-x²+2xy = -2x²+4xy-4y²

c)⅙t²+⅓k²t+⅓tk²-k²t+½t²-⅙tk²

d)u²v²+¼uv-¹/₇u²v²-uv-½uv+u²v²

Zapisz bez nawiasów:
a) -(-a)+(-b) = a-b
b) -(-a)-(-b) = a+b
c)a+(-(-b)) = a+b
d) a--(-(-b)) = a-b
e) -(-(a-b)) = a-b
f)a-(b-a) = a-b+a = 2a-b
2010-03-09T22:26:12+01:00
3a+3b-c-4a-3b+2c = -a+c
x²+2xy-3y²-2x²-y²-x²+2xy=-2x²+4xy-4y²
⅙t²+⅓k²t+⅓tk²-k²t+½t²-⅙tk²=⅔t²-⅔k²t+⅙tk²
u²v²+¼uv-¹/₇u²v²-uv-½uv+u²v²=13/7u²v²-5/4uv

-(-a)+(-b)=a-b
-(-a)-(-b)=a+b
a+(-(-b))=a+b
a-(-(-b))=a-b
-(-(a-b))=a-b
a-(b-a)=a-b+a=2a-b